Comparison of immunological properties of various bioactive combinations - Vetvicka, Vaclav; Vetvickova, Jana (Biomedical papers, 2012)
Background: Lately, more and more preparation of various cocktails or mixtures of bioactive modulators have been introduced. Their true activity is, however, rarely tested.Aim: To compare six commercially available, glucan-based immunostimulators.Methods: Immunological effects of tested combinations were measured by evaluation of phagocytosis of synthetic particles by peripheral blood neutrophils, production of IL-2 by mouse splenocytes, production of superoxide anion and nitrite oxide, antibody response to imunization with ovalbumin, and NK cell activity.Results: Our results showed that with the exception of the highest doses (phagocytosis) and superoxide anion and nitrite oxide production, only RVB 300 showed significant immunostimulative activity.Conclusion: Based on our results, we can conclude that most of the tested natural immunomodulators have limited, if any, biological effects. Only RVB 300 significantly stimulated all six tested immunological reactions.
Keywords: glucan; phagocytosis; IL-2; NK cells; antibodies